Diversification of giant and large eukaryotic dsDNA viruses predated the origin of modern eukaryotes - Guglielmini, Julien; Woo, Anthony C; Krupovic, Mart; Forterre, Patrick; Gaia, Morgan (Proceedings of the National Academy of Sciences - PNAS, 2019)
Giant and large eukaryotic double-stranded DNA viruses from the Nucleo-Cytoplasmic Large DNA Virus (NCLDV) assemblage represent a remarkably diverse and potentially ancient component of the eukaryotic virome. However, their origin(s), evolution, and potential roles in the emergence of modern eukaryotes remain subjects of intense debate. Here we present robust phylogenetic trees of NCLDVs, based on the 8 most conserved proteins responsible for virion morphogenesis and informational processes. Our results uncover the evolutionary relationships between different NCLDV families and support the existence of 2 superclades of NCLDVs, each encompassing several families. We present evidence strongly suggesting that the NCLDV core genes, which are involved in both informational processes and virion formation, were acquired vertically from a common ancestor. Among them, the largest subunits of the DNA-dependent RNA polymerase were transferred between 2 clades of NCLDVs and proto-eukaryotes, giving rise to 2 of the 3 eukaryotic DNA-dependent RNA polymerases. Our results strongly suggest that these transfers and the diversification of NCLDVs predated the emergence of modern eukaryotes, emphasizing the major role of viruses in the evolution of cellular domains.